Xanthomonas wilt of banana: Training manual - Blomme, Guy; Kearsley, Elizabeth; Ocimati, Walter; Kitumaini, Nancy Safari (2023)
Module 1: What causes Xanthomonas wilt disease and how to recognize it Module 2: How to prevent Xanthomonas wilt Module 3: Which actions to take to control Xanthomonas wilt when it is detected on a farm Module 4: Xanthomonas wilt management in practice: avoiding common pitfalls